Experimental study of dehydration processes of raspberries (Rubus Idaeus) with microwave and solar drying - Rodriguez Racca, Anabel; Bruno, Estela; Paola, Carlos; Campañone, Laura Analía; Mascheroni, Rodolfo H. (2019)
The aim of the present study was to evaluate the effect of solar and microwave drying on raspberries (Rubus Idaeus) cv. Heritage. The efficiency of drying was evaluated in terms of weight reduction in function of the time. The quality properties evaluated were color, texture, antioxidant capacity and total polyphenols content. The results showed that solar drying and microwave drying allowed a good preservation of surface color in the final product. However, the solar drying achieved a desirable texture in dried raspberries compared to microwave drying. Neither solar drying nor microwave drying allowed a high retention of the antioxidant capacity. Nevertheless, both processes allow obtaining final stable fruits (low water activity) at any time of the year.